2021
DOI: 10.1021/jacs.1c08088
|View full text |Cite
|
Sign up to set email alerts
|

Creating High Regioselectivity by Electronic Metal–Support Interaction of a Single-Atomic-Site Catalyst

Abstract: Ligands are the most commonly used means to control the regioselectivity of organic reactions. It is very important to develop new regioselective control methods for organic synthesis. In this study, we designed and synthesized a single-atomic-site catalyst (SAC), namely, Cu1-TiC, with strong electronic metal–support interaction (EMSI) effects by studying various reaction mechanisms. π cloud back-donation to the alkyne on the metal catalytic intermediate was enhanced during the reaction by using transient elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 65 publications
4
77
0
Order By: Relevance
“…[21] The EMSI can be used not only to stabilize the metal species but also to modulate the metal d-band centers by causing substantial electronic perturbations. [22][23][24][25][26][27][28][29][30] Our previous study also confirmed that EMSI can modulate the charge density of Au atoms, presenting positively charged Au + while containing charge accumulation area. [8] Therefore, tailoring the EMSI by rational coordination of Fe(III) to the support is an effective and versatile way to turn the electrons on the d orbitals of the Fe(III) into an "activation" mode, thus promoting the electron transfer.…”
Section: Introductionsupporting
confidence: 59%
“…[21] The EMSI can be used not only to stabilize the metal species but also to modulate the metal d-band centers by causing substantial electronic perturbations. [22][23][24][25][26][27][28][29][30] Our previous study also confirmed that EMSI can modulate the charge density of Au atoms, presenting positively charged Au + while containing charge accumulation area. [8] Therefore, tailoring the EMSI by rational coordination of Fe(III) to the support is an effective and versatile way to turn the electrons on the d orbitals of the Fe(III) into an "activation" mode, thus promoting the electron transfer.…”
Section: Introductionsupporting
confidence: 59%
“…Different from the characteristics of inert carbon substrates, nanocrystals typically have high catalytic activity, which modify the single metallic atoms at the interface and can regulate the local electron density at the active centers. [73][74][75][76][77][78] The impregnation method is a general strategy to synthesize nanocrystal/cluster-supported SACs, which is different from carbon-supported SACs, where galvanic replacement (GR) 79,80 and cation/anion exchange reaction 81,82 can occur on nanocrystals/clusters. Zheng et al developed a method to deposit single Pd atoms on the (100) and (110) facets of Cu nanocrystals through a GR reaction.…”
Section: Carbon-supported Sacsmentioning
confidence: 99%
“…Single-atom catalysis, a concept proposed by Zhang et al, 11 has been spread in recent years. Single-atom catalysts (SACs) have been widely studied in various reactions, including organic catalysis, [12][13][14][15][16][17] environmental catalysis, 18 oxygen reduction reaction, [19][20][21][22][23][24] water splitting, [25][26][27] hydrogen oxidation reaction, 28 nitrogen reduction reaction, 29,30 lithium-sulfur batteries, 31 formic acid oxidation, 32,33 ethanol electro-oxidation reaction, 34,35 as well as ECR. [36][37][38][39][40][41] This is mainly because the SACs with unsaturated coordination configurations and maximized metal usage endow them with descent activity and selectivity in those reactions.…”
Section: Introductionmentioning
confidence: 99%